پاک و ہند میں مطالعہ حدیث: شاہ ولی اللہ دہلویؒ کی شرح مؤطا امام مالکؒ کا تجزیاتی مطالعہ: Studies in Hadith Literature in IndoPak: An analytical study of Shah Waliullah’s Commentaries on Muwatta Imam Malik - Dr. Mubasher Hussain (MEI, 2024)
Shah Waliullah Dehlavi (d. 1762), was one of the leading scholars of the 18th-century Muslim India who made great contributions to the hadith sciences. He introduced a new method to the commentary of the hadith text and applied it in his two commentaries on the first remarkable hadith collection of Imam Malik, the eponym of the Maliki school of law. Far various reasons, unfortunately, Waliullah’s methodological approach has been ignored so far. This paper is an attempt to examine his unique and significant approach in order to draw the attention of the scholars to this overlooked area of study. For the research purpose, Waliullah’s legal opinions found in Al-Musaffa (the Persian commentary of Muwatta), have been compared with the legal preferences he articulated in his other major work titled “Hujjatullah Al-Baligha”. The conclusion reached by the writer of this paper is that Waliullah’s approach is first of its kind in the Indian Islamic history and hence needs attention for further studies, because it provides with the rules and strategies how to overcome religious extremism amongst the various Islamic sects.